2022
DOI: 10.1155/2022/1788153
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Intraarticular Injection of Platelet-Rich Plasma on Knee Osteoarthritis: A Multicenter Retrospective Clinical Study

Abstract: This study aimed to evaluate the effect of intraarticular injection with platelet-rich plasma on knee osteoarthritis. A total of 250 patients with stages I–III osteoarthritis from December 2018 to June 2020 were included in this study. All the patients had received autologous PRP injection (3 ml) into the affected knee joint every week for totally 3 injections. The VAS score and WOMAC index were used to evaluate knee function before and at 3 days, 1 month, and 3 months after injection. A total of 250 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%